Solar powered desalination - Mayere, Abdulkarim (2011)
Despite water being apparently abundant, up to half of the world’s population is faced with water crises which is growing at an alarming rate most especially in developing countries such as African countries where both physical and economic water scarcities prevail. Thus with the abundant salty water and solar intensity in the regions or seasons when water is mostly scarce, solar powered desalination presents an attractive and promising solution towards availability of clean water.